Pseudorabies in pig industry of China: Epidemiology in pigs and practitioner awareness - Tan, Lei; Zhou, Yujun; Qiu, Yixing; Lei, Lei; Wang, Cheng; Zhu, Pei; Duan, Deyong; Lei, Hongyu; Yang, Lincheng; Wang, Naidong; Yang, Yi; Yao, Jun; et al. (Frontiers in Veterinary Science, 2022)
Pseudorabies virus (PRV) is widely prevalent in China, which can transmit from pigs to other mammals. Moreover, a PRV variant isolated from an acute human encephalitis case was documented recently. It is imperative to investigate PRV epidemiology in pigs, the knowledge regarding pseudorabies (PR) and self-protection behaviors upon working among relevant practitioners including pig farmers, pig cutters, and pork salesman. In the present study, 18812 pig serum samples and 1634 tissue samples were collected from Hunan Province during the period of 2020 to 2021 for detecting the presence of PRV gE-special antibody and nucleic acids, respectively. Meanwhile, we conducted a questionnaire survey about PR among these practitioners in China. The results showed that nearly 9% (1840/20192) pigs from 161 collected sites (20.17%, 161/797) were seropositive for PRV-gE antibody. Though only 2.33% tissue samples were positive for PRV nucleic acids, all the representative PRV strains were variant. It was learned that most practitioners were frequently injured when working, the injured sites mainly included hand and foot. Among the three transmission routes of PRV, the aerosol transmission route was often overlooked. Moreover, the workers lacked self-protection awareness and were poor conscious about PRV and its potential threat to humans. All the results demonstrate that PRV remains widely spread in pig populations, while the potential threats of PRV in pig industry receive less attention, suggesting that targeted educational programs to these people should be performed.